Semantic Sensor Net: an extensible framework. (9th April 2009) - Ni, Lionel M.; Zhu, Yanmin; Ma, Jian; Luo, Qiong; Liu, Yunhao; Cheung, S.C.; Yang, Qiang; Li, Minglu; Wu, Min-you
Existing approaches for sensor networks suffer from a number of serious drawbacks, including assumption of homogeneous sensor nodes, application-dependency, engineering-orientation, and lack of interoperability. To overcome these drawbacks, we propose an extensive framework: Semantic Sensor Net (SSN). It is a framework catering for heterogeneous sensor networks, which enables dynamic tagging of semantic information to sensory data to allow more efficient and systematic monitoring and handling of environmental dynamics to provide diverse services. Semantics refers to the important meaning of sensory data, sensor nodes and application requirements. Essential semantics enables integration, exchange, and reuse of sensory data across various applications.